Active control of structures with uncertain coupled subsystems and actuator dynamics - Ningsu Luo; Villamizar, R.; Rodellar, J.; Vehi, J. (2004 American Control Conference Proceedings; Volume 4 of 6, 2004)
This paper deals with the problem of stabilizing a class of structures subject to an uncertain excitation due to the temporary coupling of the main system with another uncertain dynamical subsystem. A Lyapunov function based control scheme is proposed to attenuate the structural vibration. In the control design, the actuator dynamics is taken into account. The control scheme is implemented by using only feedback information of the main system. The effectiveness of the control scheme is shown for a bridge platform with crossing vehicle.